Comparative analysis of plasma leptin levels in both genders of patients with essential hypertension and healthy subjects - Canatan, H; Bakan, I; Akbulut, M; Baydas, G; Halifeoglu, I; Gursu, MF (Taylor & Francis Inc, 2004)
While pathogenesis of hypertension is not clearly deciphered yet, increase in body, weight, most of the time, is associated, with hypertension. There are, reports indicating that leptin, product. of the Ob gene mainly synhesized in adipocytes, may have role(s) in hypertension, but contribution of the gender is rather contradictive. In the present study, plasma leptin levels in patients of both genders With hypertension and normotensive controls were measured and the relationship between plasma leptin levels and BMI were evaluated in both sexes. Total of 62 patients (31 M/31 F) diagnosed with essential hypertension who were not under any antihypertensive medication were admitted into the study. The control group wag composed of 56 (25 M/31 F) age-, BMI- and sex matched healthy normotensive volunteers. Plasma leptin levels were determined by a commercial ELISA kit. Plasma leptin and leptin/BMI levels (Mean+/-SEM) of women (n:62) were., significantly higher than men (n:56) (20.10+/-1.47 ng/ml versus 4.72+/-0.50 ng/ml; p<0.0001). Plasma leptin and leptin/BMI levels of patients of both genders with hypertension were significantly higher than in normotensive subjects (p<0.05). Leptin and leptin/BMI levels in obese hypertensives were higher than obese normotensives (p<0.05). Obese hypertensive women had higher leptin and leptin/BMI levels than obese normotensive women (p<0.05). In conclusion, these results support the hypothesis that a possible link exists between leptin and hypertension. Further studies are needed to clarify how increased levels of leptin affects the pathophysiology of hypertension.
Keywords: plasma leptin; essential hypertension; gender